Determination of the isotopic composition of single sub‐micrometer‐sized uranium particles by laser ablation coupled with multi‐collector inductively coupled plasma mass spectrometry. (27th February 2019) - Ronzani, Anne‐Laure; Hubert, Amélie; Pointurier, Fabien; Marie, Olivier; Clavier, Nicolas; Humbert, Anne‐Claire; Aupiais, Jean; Dacheux, Nicolas
Abstract : Rationale: A multi‐collector inductively coupled plasma (MC‐ICP) mass spectrometer coupled to a UV ns‐laser ablation (LA) system was used to measure uranium isotopic ratios ( 234 U/ 238 U, 235 U/ 238 U and 236 U/ 238 U) in single uranium particles of various sizes and isotopic compositions, including home‐made sub‐micrometric natural uranium particles of narrow size distribution (415 ± 60 nm). Methods: The LA‐ICP mass spectrometer was operated in wet plasma conditions thanks to simultaneous injection of the laser aerosol and water vapor through a desolvating nebulizer. The isotopic ratios were corrected for mass bias and gain factors between detectors. The 236 U/ 238 U ratios were also corrected for the presence of 235 U hydrides and tailing of the 238 U + peak. Results: 236 U/ 238 U ratios were successfully measured in micrometer‐sized particles from the NBS U050 certified standard material with a 236 U/ 238 U ratio of ~5 × 10 −4 . The analysis of 77 natural uranium sub‐μm‐sized particles yielded a very good trueness with respect to the expected 234 U/ 238 U and 235 U/ 238 U ratios, while the measurement errors for single particles ranged from −2.7% to +2.1% for 235 U/ 238 U and from −17% to +33% for the 234 U/ 238 U ratios. Their relative combined standard uncertainties ranged from 3.3% to 32.8% and from 0.4% to 4.0% for 234 U/ 238 U and 235 U/ 238 U ratios, respectively. In addition, extremely low detection limits, in the attogram range, were achieved. Conclusions: This study demonstrates that coupling of a ns‐laser ablation system with a MC‐ICP mass spectrometer allows measurements of the isotopic composition in natural uranium particles of a few hundreds of nm with very good trueness, average combined standard uncertainties of ~1% for 235 U/ 238 U ratios and 12% for 234 U/ 238 U ratios, and detections limits of a few ag for minor isotopes.